Association of ADHD and LD with vision abnormalities among the children and adolescents in US, NHANES 1999–2004 - Lu, Jiamin; Zhou, Kefan; Liang, Yingyu; Li, Qishan; Zhong, Jiawen; Zeng, Xia; Shen, Tianran; Sun, Chongzhen; Yu, Xinping; Lu, Jinhua; Yang, Wenhan (Frontiers in Neurology, 2025)
ObjectiveTo examine the association of ADHD and LD with visual impairment, uncorrected refractive error, and refractive error (myopia, hyperopia, and astigmatism) among US children and adolescents.MethodA population-based cross-sectional study included 3,385 participants aged 12–15 years from the large, representative sample of US NHANES. The diagnoses of ADHD and LD in children and adolescents, as reported by parents or adolescents themselves, were analyzed. All participants’ right eyes were used to calculate the spherical equivalent refractive errors (SER) during the investigation. Myopia, hyperopia, and astigmatism were classified by SER. Visual acuity was categorized into normal, uncorrected refractive error (URE), and visual impairment (VI) according to objectively assessed for each eye. Logistic regression analysis was used to estimate the associations between ADHD and LD and vision abnormalities.ResultsAmong a total of 3,385 children and adolescents aged 12–15 years, 279 were reported to have a diagnosis of ADHD, and 427 were reported to have a diagnosis of LD. Compared with those without ADHD, children and adolescents with ADHD had an increased risk of hyperopia, with odds ratios (ORs) of 1.66 (95% CI, 1.03–2.67). LD was associated with higher risks of hyperopia (OR = 1.85, 95% CI, 1.17–2.90) and astigmatism (OR = 1.63, 95% CI: 1.18–2.26). After controlling for confounding variables, the results remained stable. LD also increased the risk of vision impairment (OR = 3.05, 95% CI: 1.05–8.90) after controlling for confounders. Stratified analyses showed that ADHD was a risk factor for hyperopia in boys compared with girls (OR = 1.62, 95%CI = 1.03–2.72), in 12–13-year-old individuals compared with 14–15-year-olds (OR = 1.69, 95%CI = 1.05–3.42). LD was a risk factor for hyperopia and astigmatism in girls compared with boys (OR = 2.81, 95%CI = 1.53–5.14; OR = 2.18, 95%CI = 1.22–3.90), and in 12–13-year-old individuals compared with 14–15-year-olds (OR = 1.99, 95%CI = 1.16–3.42; OR = 1.65, 95%CI = 1.07–2.56).ConclusionChildren and adolescents diagnosed with ADHD and LD may be at a greater risk of developing hyperopia and astigmatism. To accurately diagnose and treat children affected by ADHD and LD, healthcare practitioners from various medical specialties should take this association into account.